Efek Remasan Kertas Dalam Penciptaan Seni Lukis - Putra, Ida Bagus Komang Sindu (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2011)
In art work creating, ideas often come inspired by situation that is lokk loke lightly, petty, spontaneous thing. This article submit in invention process of artistic and full of aesthetics paintng creating technique. The exploration to the observation toward paper that has kneading process that causes knead texture effect as a technical marker that important in painting visualization. The paper effect is visualized in realistic and deformative way in accordance to psychological and aesthetic need of the meaning of the paper effect that is recorded in a metaphoric way. Through the concept of paper as an obtuary that cross the memories of pas experiences, these art works will become strong cultural and environmental memories analogy of many problems that emerge in contemporary art of painting. Keywords: paper, psychology, aesthetic, painting and metaphor